De múmias, huacas e ídolos: a constituição do discurso idolátrico no Peru, século XVI - Murguía, Luis Alberto Martín Dávila (Universidade do Vale do Rio dos Sinos, 2022)
This research work seeks to establish the process of constitution of the idolatrous discourse during the early colonial period, between 1532 and 1590, in the territory of the Viceroyalty of Peru. The research seeks to clarify the different moments through which a way of seeing, representing, and explaining the set of indigenous religious beliefs was configured according to a Western and Christian worldview. Using of historical sources, such as chronicles, reports, doctrines, confessionals, sermons and dictionaries, we sought to analyze how indigenous idolatries were described and the relationships established with Christian dogmas and beliefs. Thus, the idolatrous discourse begins to be constituted on elements that responded to an Aristotelian and Scholastic heritage, within a Hispanic colonial context and near the description and representation of indigenous cultural elements – such as huacas, idols and mummies or mallquis – that would be characterized as idolatrous. Likewise, the celebration of the Third Council of Lima – in 1582-1583 – and the work of the Jesuit José de Acosta, constitute a central element of the evangelization process in the Andes. It is with the analysis of the documents produced on the Council and the work of Acosta that it can be said that the process of constituting the idolatrous discourse is completed, producing an instrumentalized representation of these religious beliefs to serve the evangelization of indigenous people.

Este trabajo de investigación busca establecer el proceso de constitución del discurso idolátrico durante el período colonial temprano, entre 1532 y 1590, en el territorio del virreinato del Perú. La investigación busca esclarecer los diferentes momentos a través del cual se configuró una forma de ver, representar y explicar el conjunto de creencias religiosas indígenas según una cosmovisión occidental y cristiana. Haciendo uso de fuentes históricas, como crónicas, relaciones, doctrinas, confesionarios, sermones y diccionarios, se buscó analizar cómo se describían las idolatrías indígenas y las relaciones que se establecían con los dogmas y creencias cristianas. De esta forma, el discurso idolátrico comienza a constituirse sobre elementos que respondían a una herencia aristotélica y escolástica, dentro de un contexto colonial hispano y en torno a la descripción y representación de elementos culturales indígenas – como huacas, ídolos y momias o mallquis – que serían caracterizados como idolátricos. Asimismo, la celebración del Tercer Concilio de Lima – en 1582-1583 – y la obra del jesuita José de Acosta, constituyen un elemento central del proceso de evangelización en los Andes. Es con el análisis de los documentos producidos con motivo del Concilio y la obra de Acosta que se puede decir que el proceso de constitución del discurso idolátrico se completa, pues se produce una representación instrumentalizada de estas creencias religiosas para que sirvan a la evangelización de los indígenas.
Keywords: Peru; Século XVI; José de Acosta; Evangelização; Idolatria; Jesuítas; Century XVI; Evangelization; Idolatry; Jesuits; Siglo XVI; Evangelización; Idolatría; ACCNPQ::Ciências Humanas::História